THE USE OF “DRAW THE BANK ROBBERS” GAME IN TEACHING WRITING DESCRIPTIVE TEXTS IN JUNIOR HIGH SCHOOL - Syarifah Aini; Rusdi Thaib (Journal of English Language Teaching, 2016)
This paper is about the use of draw the bank robbers game in teaching writing descriptive texts in Junior High School. The purpose of this paper is to explain that draw the bank robbers game can be used by English teachers of Junior High School in teaching writing descriptive texts. Before applying this game, the teacher has to decide an interesting topic so that the students are enthusiastic to do this game. This game is used in pairs, the teacher provides a short description about the object will be described; the object can be a person, thing or place. Then, the teacher asks the students to draw the picture from the teacher’s description. After that, the teacher asks them to draw the new picture based on their own version about the same topic and write a descriptive text from that picture. This game can attract and motivate the students in learning writing; in addition, it is easy for the students to convey their ideas in writing descriptive text.